Connections of the juxtaventromedial region of the lateral hypothalamic area in the male rat - Hahn, Joel D.; Swanson, Larry W. (Frontiers in Systems Neuroscience, 2015)
Evolutionary conservation of the hypothalamus attests to its critical role in the control of fundamental behaviors. However, our knowledge of hypothalamic connections is incomplete, particularly for the lateral hypothalamic area (LHA). Here we present the results of neuronal pathway-tracing experiments to investigate connections of the LHA juxtaventromedial region, which is parceled into dorsal (LHAjvd) and ventral (LHAjvv) zones. Phaseolus vulgaris leucoagglutinin (PHAL, for outputs) and cholera toxin B subunit (CTB, for inputs) coinjections were targeted stereotaxically to the LHAjvd/v. RESULTS: LHAjvd/v connections overlapped highly but not uniformly. Major joint outputs included: Bed nuc. stria terminalis (BST), interfascicular nuc. (BSTif) and BST anteromedial area, rostral lateral septal (LSr)- and ventromedial hypothalamic (VMH) nuc., and periaqueductal gray. Prominent joint LHAjvd/v input sources included: BSTif, BST principal nuc., LSr, VMH, anterior hypothalamic-, ventral premammillary-, and medial amygdalar nuc., and hippocampal formation (HPF) field CA1. However, LHAjvd HPF retrograde labeling was markedly more abundant than from the LHAjvv; in the LSr this was reversed. Furthermore, robust LHAjvv (but not LHAjvd) targets included posterior- and basomedial amygdalar nuc., whereas the midbrain reticular nuc. received a dense input from the LHAjvd alone. Our analyses indicate the existence of about 500 LHAjvd and LHAjvv connections with about 200 distinct regions of the cerebral cortex, cerebral nuclei, and cerebrospinal trunk. Several highly LHAjvd/v-connected regions have a prominent role in reproductive behavior. These findings contrast with those from our previous pathway-tracing studies of other LHA medial and perifornical tier regions, with different connectional behavioral relations. The emerging picture is of a highly differentiated LHA with extensive and far-reaching connections that point to a role as a central coordinator of behavioral control.